Richard Pynson's Property in St Clement Danes, 1491–1500. (10th March 2022) - Payne, M T W
Abstract: This bibliographical note explores a previously unknown lease to the printer Richard Pynson by the Knights of St John of property in St Clement Danes, to the west of the City of London, in 1495. As well as providing further evidence for the location of Pynson's first press, it also suggests that the date of his first lease of the same property, and hence of his setting up of one of the earliest printing presses in London, was during the summer of 1491.